Research and Application of Asynchronous Programming in JavaScript - Liu, Weizhi; Li, Lin (Journal of Theory and Practice of Engineering Science, 2025)
Due to the fact that JavaScript cannot perform multiple tasks simultaneously in programming, the emergence of asynchronous programming has made these tasks no longer require queuing, but can be performed asynchronously. And with the introduction of Promise objects in ES6, JavaScript has made further improvements in asynchronous programming. This article discusses the Promise object in this regard.